Comparison of immunohistochemistry, four in situ hybridization methods and quantitative polymerase chain reaction for the molecular diagnosis of HER2 status in gastric cancer: a study of 55 cases - Staněk, Libor; Rozkoš, Tomáš; Laco, Jan; Ryška, Aleš; Petruželka, Luboš; Důra, Miroslav; Dundr, Pavel (Molecular medicine reports, 2014)
In the current study, the sensitivity and specificity of methods of HER2 status detection were studied in 55 patients presenting with gastric/gastroesophageal junction carcinoma (30 intestinal and 25 diffuse), in small biopsy (endoscopy; n=33) and resection specimens (n=22). The primary objective of the present study was to compare various methods for the assessment of HER2 status, with regards to the sensitivity and specificity of each method, as well as their concordance. In all cases, the status of HER2 was determined using immunohistochemistry (IHC), fluorescence in situ hybridization (FISH), silver in situ hybridization (SISH), and quantitative polymerase chain reaction (qPCR). The concordance rate between IHC and ISH was 100% for IHC 0 and 3+. The concordance rate for IHC 1+ was 100% between IHC and SISH, and 92.9% between IHC and FISH. The concordance rate among different FISH methods was 100%, between FISH and SISH it was 96.2%, and between qPCR and ISH methods it was 88.5%. Thus, the results demonstrate that different in situ hybridization methods are comparable and that none were superior. Furthermore, the IHC and FISH methods were found to be comparable and the concordance rate was particularly good. qPCR analysis correlated well with the other methods and appears to be a possible alternative tool for detection of the HER2 status. However, the concordance rate of qPCR with other methods was identified to be lower in the diffuse carcinoma group of endoscopy biopsy specimens; therefore investigation of further cases is required.
Keywords: dospělí; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; senioři nad 80 let; diagnostické techniky molekulární; Humans; hybridizace in situ fluorescenční; lidé středního věku; Molecular Diagnostic Techniques; Middle Aged; Aged, 80 and over; Esophagogastric Junction; In Situ Hybridization, Fluorescence; Stomach Neoplasms; imunohistochemie; mužské pohlaví; Receptor, ErbB-2; Immunohistochemistry; Adenocarcinoma; receptor erbB-2; Adult; gastroezofageální junkce; ženské pohlaví; nádory žaludku; lidé; Aged; senioři; Male; adenokarcinom; Female